2015
DOI: 10.1038/ncomms9980
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and control of the phase competition morphology in a manganite film

Abstract: The competition among different phases in perovskite manganites is pronounced since their energies are very close under the interplay of charge, spin, orbital and lattice degrees of freedom. To reveal the roles of underlying interactions, many efforts have been devoted towards directly imaging phase transitions at microscopic scales. Here we show images of the charge-ordered insulator (COI) phase transition from a pure ferromagnetic metal with reducing field or increasing temperature in a strained phase-separa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 34 publications
3
60
0
Order By: Relevance
“…Meanwhile, magnetic force microscopy (MFM) provides a nano-resolved probe of local magnetic moments in ferro-and ferrimagnets, routinely applied to visualize magnetic phase separation in manganites 16,22,23 . Using a magnetic near-field probe, we combine both SNOM and MFM techniques for collocated multi-messenger imaging of nano-scale magnetic and optical properties across the IMT.…”
Section: Multi-messenger Nano-probes and Photo-excitation Of Hidden Fermentioning
confidence: 99%
“…Meanwhile, magnetic force microscopy (MFM) provides a nano-resolved probe of local magnetic moments in ferro-and ferrimagnets, routinely applied to visualize magnetic phase separation in manganites 16,22,23 . Using a magnetic near-field probe, we combine both SNOM and MFM techniques for collocated multi-messenger imaging of nano-scale magnetic and optical properties across the IMT.…”
Section: Multi-messenger Nano-probes and Photo-excitation Of Hidden Fermentioning
confidence: 99%
“…Probes have been developed for Atomic Force Microscopy (AFM) and related SPM techniques at cryogenic temperatures and in magnetic fields [1][2][3][4] , which have enabled novel properties of magnetic and multiferroic domain walls to be explored 5,6 . Magnetic Force Microscopy (MFM) has been used to image spatially inhomogeneous magnetic textures such as skyrmions 7 and bubble domains 8,9 , and can also be used to image phase coexistence at metamagnetic phase transitions 10,11 . However, since almost all SPM setups to date have utilized laboratory superconducting magnets, the maximum field has been limited to 20 T 3 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Early investigations have revealed that the coexisting phases are controllable by electronic phase engineering. 8 The engineering method includes chemical doping, thermal annealing, electrical and/or magnetic field treatment, etc. [9][10][11]12 As a well investigated electron system, La3/8-yPryCa3/8MnO3 owns a martensitic-like electronic phase transition between the AFM/COI and the FMM phase.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11]12 As a well investigated electron system, La3/8-yPryCa3/8MnO3 owns a martensitic-like electronic phase transition between the AFM/COI and the FMM phase. 6,8 The martensitic-like phase transition allows for the coexistence of AFM/COI and FMM phase at nanometer or submicrometer scale and determines the formation of a electronic phase separation state. 13,14 Due to the vivid competition between the coexisting phases, a small external stimulus can give a remarkable change of the electronic phase separation state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation